Global warming opens the door for invasive macrophytes in Swedish lakes and streams - Hallstan, Simon (SLU/Dept. of Environmental Assessment, 2005)
Global warming opens the door for invasive macrophytes in Swedish lakes and streams The increased travelling and transporting by man has caused more species to be moved to new areas, e.g. in ballast water. These species are called introduced species or alien species. Some alien species manage to reproduce and grow rapidly in their new environment. They are then called invasive species. Invasive species is a threat against biodiversity and an economical problem. They compete with other species and can change the environment for these species. In this study aquatic plants (macrophytes) are treated. Some invasive macrophytes have such an immense growth that they are an obstacle for swimmers and anglers. Examples of aquatic species that has been introduced to Sweden and caused problems are the water weed (Elodea canadensis) and the fringed water lily (Nymhopides peltata).